2021
DOI: 10.1016/j.psychres.2021.114070
|View full text |Cite
|
Sign up to set email alerts
|

Mental health issues and health disparities amid COVID-19 outbreak in China: Comparison of residents inside and outside the epicenter

Abstract: The Coronavirus Disease-2019 (COVID-19) has exerted an impact on not only individuals who have contracted the virus but also the general public. This study compared the mental health condition of residents in the epicenter province of Hubei with that of other Chinese residents during the initial stage of the COVID-19 outbreak, and to examine emerging issues revolving around health disparities in disease prevention. A survey was administered in February 2020 to 433 Chinese adults spanning 28 regions across Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The coronavirus disease (COVID-19) outbreak was declared a pandemic by the World Health Organization (WHO) in March 2020 ( 1 ). Although a prominent concern is that the causal virus—SARS-CoV-2—may cause lethal damage to the respiratory system, scholars have also warned of the mental impacts of the COVID-19 pandemic on people living in affected regions [e.g., ( 2 , 3 )]. Depression and anxiety are the primary mental manifestations experienced worldwide during the COVID-19 pandemic [e.g., ( 4 , 5 )].…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease (COVID-19) outbreak was declared a pandemic by the World Health Organization (WHO) in March 2020 ( 1 ). Although a prominent concern is that the causal virus—SARS-CoV-2—may cause lethal damage to the respiratory system, scholars have also warned of the mental impacts of the COVID-19 pandemic on people living in affected regions [e.g., ( 2 , 3 )]. Depression and anxiety are the primary mental manifestations experienced worldwide during the COVID-19 pandemic [e.g., ( 4 , 5 )].…”
Section: Introductionmentioning
confidence: 99%
“…We know, China, the first country affected by the COVID-19, revealed that the case fatality rate was 8% amongst 70-79 years, which was almost double among the individuals aged 80 years or more (Wu & McGoogan, 2020). Chinese evidence also suggests strategies are required to reduce the adverse psychological and occupational impacts on healthcare workers (HCWs) and the population in a lockdown reported as poor psychological wellbeing (Cheng et al, 2021;Meng et al, 2020;Zhang et al, 2021). At the beginning of the outbreak of COVID-19 healthcare system of China experienced intrinsic problems-public hospitals being overwhelmed, a dire shortage of personal protective equipment, and exhaustion of health human resources and resource costs, leading to the widespread and exponential rise of infected cases at the early stage of the epidemic (Sun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is still raging in countries such as India, Australia and others. The outbreak and rapid spread of COVID-19 harmed physical health and brought severe mental health problems among the public (Cheng et al , 2021). Zhu et al (2020) regarded psychological crisis as a secondary disaster, which should not be ignored by the government as well as the public.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental risk perception has a direct negative influence on perceived socioeconomic development and subjective total well-being (Xu et al , 2017). In the face of major pandemic emergencies, the public experience common psychological negative responses, such as stress, worry, mental distress, mood problems, sleeplessness, anxiety, grief, depression, boredom, loneliness, suicidal ideation, denial, fear, frustration, anger, and so on (Cheng et al , 2021; Mukhtar, 2020). If this state is not regulated and balanced in time, it will be vulnerable to the autoimmune system and cause long-term mental and psychological trauma, so that later the evasion, impulsivity, robbery, or fights will frequently occur later in life.…”
Section: Introductionmentioning
confidence: 99%